Evidence of Cross-Cultural Consistency of the S-Five Model for Misophonia: Psychometric Conclusions Emerging From the Mandarin Version - Vitoratou, Silia; Wang, Jingxin; Hayes, Chloe; Wang, Qiaochu; Stefanatou, Pentagiotissa; Gregory, Jane (Frontiers in Psychology, 2022)
Misophonia is a disorder generally characterised by a decreased tolerance to everyday sounds. Although research is increasing in misophonia, a cross-cultural validation of a psychometric tool for measuring misophonia has not been evaluated. This study investigated the validity of the S-Five multidimensional model of the misophonic experience in a sample of Chinese participants. The S-Five was translated in a forward-backward method to Mandarin to establish a satisfactory translation. The translation was also independently back translated to English, with no significant differences when compared to the original S-Five. Through exploratory factor analysis, using responses from 256 Chinese individuals, the five dimensions (internalising appraisals, externalising appraisals, perceived threat and avoidance behaviour, outbursts, and impact on functioning) were replicated, indicating the cross-cultural uniformity of the experience of misophonia as captured by the S-Five. That is, current results point to the stability of the manifestation of misophonia across cultures, seen here for the first time in the literature. By design, the S-Five items were developed to reflect sound sensitivities in a manner that is not specific or matching to individuals of a certain age, gender, ethnicity, nationality, socio-economic status, and educational level. Testimonial to this fact is not only the replication of the five factors, but also the replication of the evidence towards satisfactory psychometric properties (reliability and validity) of the scale. Based on the results of this study, the S-Five is a psychometrically robust tool to be used within the Chinese population.